Parasites and RNA viruses in wild and laboratory reared bumble bees Bombus pauloensis (Hymenoptera: Apidae) from Uruguay - Salvarrey, Sheena (2021)
Bumble bees (Bombus spp.) are important pollinators insects involved in the maintenance of natural ecosystems and food production. Bombus pauloensis is a widely distributed species in South America, that recently began to be managed and commercialized in this region. The movement of colonies within or between countries may favor the dissemination of parasites and pathogens, putting into risk while populations of B. pauloensis and other native species. In this study, wild B. pauloensis queens and workers, and laboratory reared workers were screened for the presence of phoretic mites, internal parasites (microsporidia, protists, nematodes and parasitoids) and RNA viruses (Black queen cell virus (BQCV), Deformed wing virus (DWV), Acute paralysis virus (ABCV) and Sacbrood virus (SBV)). Bumble bee queens showed the highest number of mite species, and it was the only group where Conopidae and S. bombi were detected. In the case of microsporidia, a higher prevalence of N. ceranae was detected in field workers. Finally, the bumble bees presented the four RNA viruses studied for A. mellifera, in proportions similar to those previously reported in this species. Those results highlight the risks of spillover among the different species of pollinators.